Tonality of Showing Russian Position in English Speaking Mass Media during Sanction Period - L. E. Khrustova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2020)
Highly charged political environment, which is peculiar to the current stage of international relations  development, is accompanied by an extensive media war. The problem of showing Russia on the negative side in international press was known and discussed since early 2000-s. Russian-Ukrainian conflict which started at  the end of 2013 – beginning of 2014 provoked foreign mass media to make a point of Russia and enhance the quantity of adverse statements towards the country. It seems that the aim of foreign mass media is to form an antagonistic image of Russia among the audience. The research under discussion is devoted to the problem of  the sentiment of showing Russia in English speaking mass media under the influence of Russia sanctions. News texts for period from 2012 till 2018 were analyzed. The whole period was divided into several stages: the first  stage is connected with period before sanctions; the others reflect different phases of restrictions’ imposition.  The authors suggested that foreign mass media is inclined to show Russia on the negative side irrespective of  the contents of political situation during the sanctions period. To approve this statement a detailed text analysis was provided to find out the following indicators: the total quantity of news, connected with Russia, in the stated period; the quantity of positive and negative words. It was found out that the sanctions imposition provoked the increase of total Russia media hits, but the increase of negative words was higher than the increase of positive words. Reviewing the contest of news from the perspective of correlation between the words showed that Russia-Ukrainian conflict  theme lost its significance, but the total level of enmity in news text remained the same and even has the tendency of increasing in line with the other political events.